(untitled) (مجلة المنصور, 2022)
This research aims to determine the nature of the strategic flexibility relationship and its impact on the rationalization of strategic decisions in business organization. Strategic flexibility forms the basic engine for all the changes that the organizations can do to adapt to the environment in which it operates. Besides, the rationalization of the strategic decisions taken by senior management helps the organization to stay and continue to work through the exploitation of the opportunities and to avoid threats posed by the surrounding environment. The problem of the research has indicated that there is a clear lack of employment of strategic flexibility to rationalize the strategic decisions of the organization surveyed. The General Company for Vegetable Oils has selected as a field of application. The research sample is a simple random one, consisting of 76 members of the human resources in the company already mentioned . a questionnaire has been prepared on the basis of a number of ready measures after being subjected to tests of validity and reliability. The ready- made statistical program (SPSS) is used in the introduction and analysis of the research date. Among the statistical tools used in the analysis are: “the percentage of recurrence, the arithmetic means standard deviation, coefficient of variation, the link of the Spearman coefficient and simple linear regression” . The statistical tools have had results, most of which, has an association with and the impact of moral significance for strategic flexibility in the rationalization of strategic decisions. Accordingly, the major and minor assumptions of the research have been accepted. The research has recommended the need of the surveyed organization to identity the most important strategic flexibility aspects which could be invested in the rationalization of its strategy.